Individual unemployment & its consequences: a regional perspective - Ball, Philip Bokang (2012)
Unemployment has a strong influence on the economic prospects of the UK economy as a whole. The effect of unemployment can be long-lasting, and as an experience can imply lasting effects on future employment outcomes. In order to avoid unemployment, individuals may decide take jobs they are overqualified for as a stepping stone to a better match when such positions become available. If over-qualification is a negative productivity signal, then this could reduce future career mobility. This thesis aimed to gain some insights into the impact of where individuals live, within the UK, on their unemployment and employment experiences. With that in mind, detailed data sets were constructed in order to answer the questions of interest. Moreover, flexible econometric techniques were employed.